On the use of calibration sensors in source localization using TDOA and FDOA measurements - Li, Jinzhou; Guo, Fucheng; Yang, Le; Jiang, Wenli; Pang, Hongwei (Digital signal processing, 2014)
The accuracy of a source location estimate is very sensitive to the presence of the random noise in the known sensor positions. This paper investigates the use of calibration sensors, each of which is capable of broadcasting calibration signals to other sensors as well as receiving the signals from the source and other calibration sensors, to reduce the loss in the source localization accuracy due to uncertainties in sensor positions. We begin the study with deriving the Cramer–Rao lower bound (CRLB) for source localization using time difference of arrival (TDOA) and frequency difference of arrival (FDOA) measurements when a single calibration sensor is available. The obtained CRLB result is then extended to the more general case with multiple calibration sensors. The performance improvement due to the use of calibration sensors is established analytically. We then propose a closed-form algorithm that can explore efficiently the calibration sensors to improve the source localization accuracy when the sensor positions are subject to random errors. We prove analytically that the newly developed localization method attains the CRLB accuracy under some mild approximations. Simulations verify the theoretical developments. •We introduce calibration sensor, which can both emit and receive signals.•We focus on source localization using TDOA and FDOA measurements.•The CRLB is derived for source localization using calibration sensors.•The proposed method is better than the method only using normal sensors.•The proposed method is also better than the method using extra calibration emitter.